2023
DOI: 10.3389/fimmu.2022.910236
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium vivax vaccine: What is the best way to go?

Abstract: Malaria is one of the most devastating human infectious diseases caused by Plasmodium spp. parasites. A search for an effective and safe vaccine is the main challenge for its eradication. Plasmodium vivax is the second most prevalent Plasmodium species and the most geographically distributed parasite and has been neglected for decades. This has a massive gap in knowledge and consequently in the development of vaccines. The most significant difficulties in obtaining a vaccine against P. vivax are the high genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 266 publications
(431 reference statements)
0
10
0
Order By: Relevance
“…Here, our results demonstrated that a nucleoside-modified mRNA–LNP vaccine encoding Pvs25 can induce cellular as well as durable antigen-specific antibody responses with potent parasite transmission-blocking activity in mice, providing strong support for further preclinical testing in nonhuman primates. Given the positive results, it seems worthwhile to apply the mRNA–LNP platform to other P. vivax vaccine antigen candidates 49 and potentially evaluate multivalent P. vivax mRNA–LNP vaccine formulations as successfully shown for influenza virus 50 53 . The platform has the potential to overcome the challenges of poor immunogenicity, strong reactogenicity, low potency, and short-lived immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Here, our results demonstrated that a nucleoside-modified mRNA–LNP vaccine encoding Pvs25 can induce cellular as well as durable antigen-specific antibody responses with potent parasite transmission-blocking activity in mice, providing strong support for further preclinical testing in nonhuman primates. Given the positive results, it seems worthwhile to apply the mRNA–LNP platform to other P. vivax vaccine antigen candidates 49 and potentially evaluate multivalent P. vivax mRNA–LNP vaccine formulations as successfully shown for influenza virus 50 53 . The platform has the potential to overcome the challenges of poor immunogenicity, strong reactogenicity, low potency, and short-lived immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these ndings contribute to understanding the antibody response to P. vivax infection, particularly to the correlates of protection. Deeper analyses are required for the identi cation of potential surrogate markers or signatures of immune protection using systems biology 5,30,60,61…”
Section: Discussionmentioning
confidence: 99%
“…Currently, only three P. vivax antigens, the circumsporozoite protein (PvCSP) 12,28,[31][32][33] , sexual-stage ookinete surface protein (Pvs25) 2,3,34 , and P. vivax Duffy-binding protein (PvDBP) 35 have reached vaccine clinical development phases (Phase Ia, Phase IIa/b). However, several others are in preclinical development and discovery phases 21,29,30,36,37 . Nevertheless, which of these are responsible for protection remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…21,27,28 Therefore, the development of new vaccine targets and effective drugs to combat malaria is increasingly necessary. 2729 In addition, vivax malaria has re-emerged in regions considered malaria free. 21,30,31…”
Section: Vivax Malariamentioning
confidence: 99%
“…21,27,28 Therefore, the development of new vaccine targets and effective drugs to combat malaria is increasingly necessary. [27][28][29] In addition, vivax malaria has re-emerged in regions considered malaria free. 21,30,31 Among the Plasmodium species, P. vivax is most closely related to P. cynomolgi, the species responsible for infection in Asian monkeys.…”
Section: Vivax Malariamentioning
confidence: 99%